МОДЕЛЮВАННЯ ФЕРОРЕЗОНАНСУ В ТРАНСФОРМАТОРАХ НАПРУГИ З УРАХУВАННЯМ ЕФЕКТУ СТАРІННЯ СТАЛІ - Тугай, Ю.І.; Бесараб, О.Б. (Інститут електродинаміки НАН України, Київ, 2014)
The voltage transformer is one of the main sources of information, which is necessary for optimal control in the electric power systems. Its outage as result of ferroresonance process provokes severe emergency state with significant harm. So the study of this process is very important and urgent task. But the traditional analytic approach gives the qualitative not quantitate result rather. Therefore, the digital simulation is more useful for this goal. The adequate simulation is necessary for the hazard identification. It should be remembered that ferroresonance process is highly sensitive to different factors. So effect of change of the magnetization curve as result of the aging steel should be taken into account too. The influence of steel aging on the ferroresonant process was analyzed by the Giles-Atherton model and the expanding of hazardous zone was shown. Therefore, the dangerous process may appear in unexpected place and it's necessary to check the emergence of ferroresonance condition in substation switchgear periodically. References 7, figures 3.